Jan Jerzyczek – a resident painter of the Calvary complex in Kalwaria Zebrzydowska - Mirosław Płonka (Folia Historica Cracoviensia, 2021)
The art of resident monastic painter Jan Jerzyczek (1788-1842) is paradoxical, as his technical skills and painting technique were categories as folk art even though the artist himself copied 17th century work and his paintings are based on 16th century Antwerpian engravings as well as his own experience of the Calvary’ mystery plays. Authors of monographs on the Calvary complex barely mention Jerzyczek, yet even without providing a historical, economic, and political context of the job of a resident monastic painter in the early 19th century, due to which they fail to notice the phenomenon of Jan’s paintings in the course the changes that were in progress at that time. The aim of this article is to organise knowledge on Jerzyczek’s activity and work in the Calvary, which would serve as the basis for determining the iconography of original Calvary scenery and images which were removed in the course of the first comprehensive ‘maintenance’ of the Polish Jerusalem under the supervision of Gaudenty Thynell OFM. At the same time, a closer look at Jerzyczek’s paintings allows us to perceive the visual arts (mainly painting) in the Calvary in the first half of the 19th century as a replacement for the mystery play scenes removed after 1772, the observance of which (according to Austrian authorities) was incompatible with the solemnity of the service. Jerzyczek’s art is also paradoxical in that he was much better at painting pictures inspired by his own participation in Calvary mystery plays when personal experience prevailed over his printed influences.